Legalitas Pemberhentian Ketua Badan Permusyaratan Desa Oleh Kepala Desa - Rumalean, Suwardi; Pattinasarany, Yohanes; Matitaputty, Merlien Irene (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2024)
The Village Government carries out various village government activities which are contained in the statutory regulations. This research aims to find out and analyze whether the action of dismissing the Chair of the Village Consultative Body by the Village Head is not legal. To find out and analyze the impact and legal consequences that occur regarding the actions of the Village Head who do not have legality in dismissing the Chair of the Village Consultative Body. This research includes normative juridical. 1. The results of the research are based on Articles 12, 14, 15, 17, 18, 19, 20, 21, 27, 28, 29, 30, 32, 33, 34, 35, 46, 47, Article 63 of Permendagri 110 of 2016 concerning Village Consultative Body, and Articles 55, 56, 58, 59 of Law Number 6 of 2014 concerning Villages, the village head does not have direct authority to dismiss members/leaders of the Village Consultative Body or appoint new members of the Village Consultative Body. So the dismissal of the Chairman of the Village Consultative Body carried out by the Village Head has no legality. The Legal Consequences if the action of dismissing the Chairman of the Village Consultative Body by the Village Head who does not have legality is null and void, as well as the Legal Consequences of the village head's legal action being declared null and void in the first place based on invalid authority and not fulfilling the provisions of the provisions which must be fulfilled in order for a village head's actions to be declared valid.